Digital Play, Is It True Play? - Masud, Sitti Habiba; Jalal, Fasli; Yetti, Elindra (Exploration in Early Childhood Research, 2024)
In the past, playing was done offline, and various tools or physical resources were usually used to support the play (non-digital play). As time goes by and the digital era enters, a new classification of play is discovered, namely playing using technological devices (digital play) (Marsh et al., 2016; Undheim, 2022a). However, this raises the question of whether digital play has the same essence in terms of play, which is supported by play theories that can support children's development. This research focuses on the concept of digital play in early childhood. This study utilizes a literature review. Data were collected through Preferred Reporting Items for Systematic Review and Meta-Analyze Extension for scooping reviews using 3 databases, namely; Google Schoolar, Science Direct anda Taylor & Francis Online Journal databases. The presentation brings out the concept of digital play with the support of play theory and its influence on early childhood development then how teacher support digital plat, which will be used in the research to seek advice from the audience. The concept will provide an improved understanding of digital play for early childhood